The Southern Man through a Northern Eye : The Southern Gentleman in Joyce Carol Oates’s The Accursed (2013) and Carthage (2014) - Tanya TROMBLE (Babel: Littératures Plurielles, 2015)
This article discusses the ways in which the gentleman characters in Joyce Carol Oates’s novels The Accursed and Carthage are identified with notions of displacement, and examines the ways in which the evocation of stereotypes contributes to the identification of each character as a “southern gentleman.” Oates creates two characters on the edge of their communities, men for whom the “gentleman” is a persona they adopt to varying degrees of success. She deconstructs the myth of regional exceptionality in The Accursed by showing a southern gentleman and a northern pastor who fall prey to the same moral weaknesses. In Carthage¸ the Investigator’s ability to conjure the gentleman type emphasizes the artificiality of this mythical southern character.